SCIENTIFIC DISCOURSE IN ARTISTIC LITERATURE - Asratyan, Zoya; Sadrieva, Guzel; Potanina , Aleksandra; Kiselevskaya, Varvara (Revista Inclusiones, 2020)
The article distinguishes between the language of real life (a vital one) and the language of imaginary literature (an imaginary one). The aim of the article is to describe how a scientific discourse is presented in fictional works. The authors discuss the main characteristic features of text and discourse and underline the differences between them. Linguistic means of a scientific discourse or scientific functional style are analyzed on the material of the contemporary British writer D. Lodge’s imaginary prose. It is shown how vital scientific discourse is being reflected in literary texts. The article also deals with some ways and methods of creating ironic and satirical effects. Discourse zeugma is suggested as one of such means